Analisis Kinerja Keuangan Kota Mojokerto Dengan Pendekatan Value For Money - Mulyanigtyas, Mulyanigtyas (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
In applying the central government policy, city of Mojokerto can absorb the budged in 2016 up to 91 % from APBD amount Rp 1,007 trillion. Then in periode of 2017 the number decreased  became 10% into Rp 915 million. In the realization of budget utilization statement that issued by Income Financial Management dan Assets Institution of Mojokerto government, the deficient of activites implementation make funds realized amount Rp 83.575.497.292 was abortive to utilize. Because of that BPPKA should concern on value for money to implement the activities. This research aims to determine how is financial performance of BPPKAMojokerto for fiscal period of 2013-2015, by using value for money approach in economy, efficiency, and effectivityâs term.This research using describtive with quantitativeapproach.This research conducted in Income Financial Management dan Assets Institution of Mojokerto Government. The sources of the data in this research areusing literature study method and documentation. The data analysis techniques is quantitative describtive by formula: economic ratio, efficiency ratio, effectiveness ratio. Based on the results of the research, it is known that financial performance criteria of BPPKA for fiscal period of 2013 included in quite economical, quite efficient, and very effective. In the fiscal period of 2014 the evaluation of financial performance criteria rating were quite economical, less of efficient, and ineffective. Then in the fiscal period of 2015, the eveluation of financial performance criteria included in quite economical, less of efficient, and very effective.